Analisis Penerapan PSAK No.36 Mengenai Pengukuran dan Pendapatan Serta Penyajian dalam Laporan Keuangan Pada PT.Asuransi Jiwasraya (Persero) - Sahatiqah, Utari B1031131010 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACT Life insurance has different characteristic with other types of business, so that transaction of insurance and treatment of accountancy on the insurance company become typically. Therefore, as a guidance in execution of life insurance, specified by a special standard arranging life insurance that is Statement of Financial Accounting Standard ( PSAK) No. 36 about recognition and measurement of revenue. This research was conducted at PT. Asuransi Jiwasraya ( Persero) with the aim to find out how the recognition and measurement of revenue as well as it’s presentation in the financial statements and to find out what the constraints faced by firms in the recognition and measurement income. The data was collected by interviewing techniques, documentary study, book study questionnaire. Data analysis techniques include methods of descriptive and comparative methods with PSAK No. 36 and the result of the questionnaire as a tool of analysis. The result illustrate that the company’s revenue recognition principle has been almost entirely in accordance with PSAK No. 36 where the company’s main revenue comes from premium income, investment and other income. Recognition of premium income over the accrual made at the time of occurance, rather than when cash or cash equivalents received. Measurement of the value that must be recognized is the fair value of consideration received, which is determined with the consent of both parties, the corporate and service users. For the presentation of financial statements, income statements are presented in a single step has also been in accordance with PSAK No. 36. Technically, companies do not face constraints in the recognition and measurement of income. Constraints currently facing is related to changes in reporting standards of financial accounting standards to IFRS 4. Keywords          :    PSAK No. 36, Revenue Recognition, Earnings Measurement, Financial Statement, Life Insurance